If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 9 = -79x + -7x Reorder the terms: 9 + 4x = -79x + -7x Combine like terms: -79x + -7x = -86x 9 + 4x = -86x Solving 9 + 4x = -86x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '86x' to each side of the equation. 9 + 4x + 86x = -86x + 86x Combine like terms: 4x + 86x = 90x 9 + 90x = -86x + 86x Combine like terms: -86x + 86x = 0 9 + 90x = 0 Add '-9' to each side of the equation. 9 + -9 + 90x = 0 + -9 Combine like terms: 9 + -9 = 0 0 + 90x = 0 + -9 90x = 0 + -9 Combine like terms: 0 + -9 = -9 90x = -9 Divide each side by '90'. x = -0.1 Simplifying x = -0.1
| 2x-3x-8x-3=0 | | 6n-18=4n+8.4 | | 3x+1=b | | 14t=8 | | 7+2x+2=2x+9 | | 5x+6-3= | | 8x^2-14x-5=0 | | 2a+4-8a-10= | | 5x+4=7x+7-2x | | 2x+38=x+29 | | 1.20=0.20x+0.40 | | 42-3x=6x+19 | | 219-4x=32x+15 | | 1.90=0.30x+0.40 | | 2(4x-3)=3(x-1) | | -1-6x=11-10 | | 6(r+2)-4=10 | | 12x+4=4x+5 | | 9x+5y=47 | | 2b/3+6=24 | | 13x+2=6x+15 | | 9r+5=24+10r | | -8.4=-6 | | 2x+2-10=12 | | 4k-6=k+12 | | 0*0= | | 3c+5c=32 | | 105-2x=34x+17 | | 251-6x=39x+16 | | 2(n+7)=7-5(n-7) | | 12-3x=5x+6 | | x*2-18+x*2=62 |